Efeitos de sentidos sobre o trabalho dos professores de língua materna: uma abordagem sobre a produção do discurso pedagógico - Brittes, Letícia Ramalho (2011)
This work is a Master Thesis on Education, related to research interest number two School Practices and Public Policy. It s linked to the Program of Post-graduation on Education of the Federal Santa Maria University (Brazil). This study had the proposal from the discourse analysis of mother tongue teacher s in Elementary School at investigating the pedagogic discourse production in school environment, specifically during the class, understanding this discourse as teacher s work. This research had the participation of six Portuguese teachers of municipal public school in Santa Maria RS Brazil. It s understood that the planning and conduction of the lesson itself is the teacher s work, however, for that, it s necessary the language mediation. The aim of this study was to analyze how the language in discourse, used by teachers during the class, are produced as work. Besides, it intended to investigate the meaning effects of these professionals work, observing how pedagogic discourse circulates in class, producing and reproducing the values of the society immersed on the capitalist production mode context. So that, this research had as theoretic-methodological approach the Discourse Analysis of French School, founded by Michel Pêcheux on 1960 s. The study is also based on Historical- dialect Materialism to develop the discourse analysis. This investigation was built by observation, recording and transcription of the discourses, constituting, in this way, the research corpus, that was analyzed during and after the observations realized at schools. Thus, I d intended, through this study, to contribute with the research on teachers work, issue in which I insert my academic investigation interest. At this sense, I believe to have researched about meaning effects on teachers work meant, for me, to have entered on the language non-transparence, through a reading gesture, can interpret what is being said, hidden, unsaid and that was already said, from social places occupied by the teachers.